REMO - uma aplicação para especificação de requisitos ágil e modelagem de sistemas - Trentin Junior, Sergio (2021)
With technological advances and the spread of technology, there was an increase in the search for quality software products at a reduced cost. This increase directly reflected the complexity and agility of software development processes. In this context and in the search for quality software development, the use of tools became inevitable. However, finding tools capable of adapting to processes and contemplating different functionalities can be difficult. In terms of requirements engineering, it would be no different, a tool that covers the entire process of specifying requirements in agile methodologies and systems modeling continues to be a challenge, requiring the use of tools in parallel. Therefore, the objective of this work is the initial development of a web tool capable of meeting the requirements specification in agile methodologies and systems modeling, called REMO. The tool comprises three modules: Project Management, Agile Requirements Specification, and Software Modeling. This work includes the development of project management modules and agile requirements specification. In addition, a case study was also carried out to assess the effectiveness of the tool in the context of usability and agility. The results achieved showed positive thinking in relation to the use of REMO and the continuity of its development.